Health diagnosis of coastal zone ecosystem: China's case - Zhang, Cai; Wang, Miao (Frontiers in Public Health, 2023)
In this study, the ecosystem health model, state space model and ecological health early warning principle were comprehensively applied to construct the coastal ecosystem health diagnosis framework of “Carrying type →Early warning degree →Health level”; The evaluation index system of coastal ecosystem carrying capacity was established; Taking Shandong Province as the empirical research object, the health status of the coastal ecosystem in Shandong Province was diagnosed by using the relevant data from 2007 to 2019. The empirical results show that: 1) From 2007 to 2013, the carrying capacity of the coastal ecosystem in Shandong Province was relatively good, in the state of “loadable” or “critical overload”, while from 2014 to 2019 (except 2017), the carrying capacity was poor, in the state of “overload”; 2) From 2007 to 2013, the early warning degree of coastal ecosystem health in Shandong Province was in the state of “no alarm”, “light alarm” and “medium alarm”, and the health level was in the state of “very healthy”, “healthy” and “sub-health”; from 2014 to 2019 (except 2017), the health warning level of the coastal ecosystem in Shandong Province was in the state of “serious alarm” and “extremely serious alarm”, and the health level was in the state of “unhealthy” and “Morbid”, and the health status was worrying; 3) The key influencing factors affecting the carrying capacity of the coastal ecosystem mainly included the output of marine mining, marine GDP, per capita marine production, total amount of main pollutants directly discharged into the sea, domestic tourist arrivals in coastal cities, area of marine nature reserves, proportion of class IV and inferior class IV seawater, average density of beach garbage in the monitoring area, number of medical and health institutions; Finally, some policy suggestions were put forward to improve the health of coastal ecosystem in Shandong Province.